Development and evaluation of packaging prototypes in a teaching context of ergonomic design: A didactic experience - Bonfim, Gabriel [UNESP]; Medola, Fausto [UNESP]; Paschoarelli, Luis [UNESP] (Springer Nature, 2017)
The teaching of ergonomic design of packages requires an experience of prototype development that can be evaluated and compared with similar commercially available products. This study was aimed to report an experience of development and evaluation of consumable product packages in a teaching context of ergonomic design. Videos were recorded to assess the perceived usability of packages and prototypes. It was applied SUS and SD protocols to evaluate the products. The teaching experience in assessing consumer products packaging, the use of assessment parameters in the design of new packages and the development of prototypes that meet aesthetic, functional and especially ergonomic requirements, were expressively positive to the comprehension of the process by the actors (students) involved.
Keywords: Ergonomics; Package design; Prototypes; Teaching